Genre-based teaching cycle and instructional design for teaching texts and mandated curriculum contents - Anita Triastuti; Suwarsih Madya; Philip Chappell (Universitas Pendidikan Indonesia, 2022)
This study aimed to construct a genre-based teaching (GBT) model for accommodating the Indonesian EFL curriculum. Anchored in two current GBT cycles developed by Derewianka and Jones (2016) and Chappell (in preparation), a modified GBT cycle and the following instructional design model were constructed. This design-based study conducted its first two stages: the analysis of practical problems and the development of solutions based on the existing knowledge. The practical problem analysis was executed through four exploratory studies of the analyses of instructional documents, open-ended reflective questions, English textbooks, and literature. The exploratory studies reveal context-specific problems of GBT implementation which suggest the need for the provision of a GBT model to guide the enactment of teachers’ GBT practices. The development of solutions was achieved by carefully modifying a GBT cycle informed by principled eclecticism and designing a series of instructional steps which offer three strands for teaching texts and systematic ways for integrating the mandated contents of the Indonesian EFL curriculum. The constructed GBT model is to provide a systematic instructional organization for teaching texts, developing English language skills, and incorporating varied mandated instructional contents of the Indonesian EFL curriculum and to illustrate a construction process of a GBT model to accommodate varied contents of EFL curriculum.